Kinerja Konselor dalam Mempersiapkan Generasi Emas pada Masyarakat Multi Kultural dan Modern - I Made Olas Astawa (Jurnal Penjaminan Mutu, 2016)
Councellor is a noble, dynamic, always happy profession that relates to life. It is dedicated as prevention, development, exploration, change, and remedies for indivduals living in modern multicultural world. In recent days councelling is not only needed in schools but also by societies in accordance with the Regulation from the Minister of Education No. 27 /2008 on the Standard for the Academic Qualification and Competence of Councellor.